Chronic Uveitis Following Neodymium-Doped Yttrium Aluminum Garnet Laser Peripheral Iridotomy. Issue 10 (October 2017) - Ali, Amro; Rosenfeld, Cyril; Rosenberg, Eric; Sharma, Sansar; Wandel, Thaddeus L.
Abstract : Purpose: Assessment of a chronic uveitis entity in nonuveitic patients following neodymium-doped yttrium aluminum garnet (Nd:YAG) laser peripheral iridotomy. Methods: A 7-year retrospective observational case series of 5 patients that developed chronic uveitis following a Nd:YAG laser peripheral iridotomy treatment. Results: Five eyes of 5 nonconsecutive patients had developed chronic anterior uveitis lasting >12 weeks. Four patients were female, with a mean age of 60.3 years (range, 48 to 83 y), and a mean follow-up duration of 8 months after initiation of treatment. Conclusions: Chronic anterior uveitis should be addressed as a possible risk in patients undergoing Nd:YAG laser iridotomies. A larger prospective study would be necessary in establishing and exploring the association between these 2 entities.